2015
DOI: 10.1007/s00405-015-3709-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tissue glue in wound healing of head and neck patients undergoing neck dissection

Abstract: We investigated the impact of fibrin glue on postoperative drainage amount and duration in head and neck cancer patients who underwent neck dissection. This study was a prospective randomized controlled trial. Patients who were scheduled to undergo neck dissection due to head and neck cancer were eligible for this study. After receiving a detailed explanation, all patients signed an informed consent form before enrollment. Patients were then randomly assigned to the study group (fibrin glue) or control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…included patients having central neck dissection, whereas Vidal‐Perez et al . included patients having central and lateral neck dissections), one at lateral neck dissection, one at parotidectomy and five at rhytidectomy . Only six of the included studies reported a sample size calculation and only three of these reached the planned sample size.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…included patients having central neck dissection, whereas Vidal‐Perez et al . included patients having central and lateral neck dissections), one at lateral neck dissection, one at parotidectomy and five at rhytidectomy . Only six of the included studies reported a sample size calculation and only three of these reached the planned sample size.…”
Section: Resultsmentioning
confidence: 99%
“…None of the five trials in which patients dropped out after randomisation performed an “intention‐to‐treat” analysis. They were considered at high risk of attrition bias if the number of dropouts were unequal between the two groups of patients . Four trials pre‐registered their protocol on ClinicalTrials.gov so that a comparison between the planned outcomes and reported outcomes could be made and assessment of reporting bias possible .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations